Pro-estrogenic and anti-inflammatory effects of Corchorus olitorius and Amaranthus hybridus leaves in DMBA-induced breast cancer - Omoremime E. Dania; Titilope M. Dokunmu; Bose E. Adegboye; Alaba O. Adeyemi; Favour C. Chibuzor; Emeka E.J. Iweala (Elsevier, 2024)
Background: Breast cancer is the world's most prevalent cancer and accounts for the most lost disability-adjusted life years in women worldwide. Tumour-promoting inflammation and sustained proliferative signaling are some hallmarks of cancer which can be activated by environmental carcinogens that induce oxidative stress and inflammation via increased interleukin-6 (IL-6) secretion. Increased binding of estrogen promotes the development and proliferation of breast cancer. Phytochemicals have been reported to promote health by combating oxidative stress. Purpose: This study aims to assess the potential of crude hydroethanolic extract of C. olitorius (CO) and A. hybridus (AH) singly and in combination on IL-6 and estrogen in DMBA-induced breast cancer in rats. Study design: A 9 × 6 animal model made up of three groups each of control (normal, negative, positive), chemopreventive, and therapeutic (CO, AH, CO + AH mix). Methods: Phytochemical analyses were carried out on the plants, and breast cancer (BCa) was induced in female Sprague-Dawley rats by administering 80 mg/Kg BW DMBA single dose orally. ELISA kits were used to determine the levels of IL-6 and estradiol in plasma. Results: The group administered Tamoxifen and a combination of both plants recorded significantly higher plasma levels of estradiol (p = 0.0005 and p = 0.0242) respectively. Chemopreventive AH and CO + AH mix (39.46 ± 3.167; 39.69 ± 1.837) respectively had IL-6 levels similar to the normal control (38.03 ± 2.334) and less than in the corresponding therapeutic groups (60.75 ± 13.08;57.88 ± 15.32) suggesting synergistic effect of both plants. Conclusion: A. hybridus can better prevent inflammation. We propose that the plants possess pro-estrogenic and anti-inflammatory potentials.